2023
DOI: 10.1108/srj-03-2023-0125
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ESG disclosure into the relationship between CSR and green organizational culture toward green Innovation

Abstract: Purpose This study aims to propose a conceptual framework to examine the impact of corporate social responsibility (CSR) and green organizational culture (GOC) on green innovation with the moderating role of environmental, social and governance (ESG) disclosure in the Malaysian manufacturing industry. Design/methodology/approach The study is based on primary data to be collected from 204 manufacturing enterprises of consumers, products and services sector through a questionnaire that incorporates the five-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…According to Chen et al (2006), green innovation refers to designing pro-environmental products and processes that mitigate pollution, recycle waste and preserve energy. It tries to make the product more environmentally friendly through engaging in a gamut of activities such as using greener raw materials, decreasing carbon emissions, reducing the consumption of non-renewable sources of energy, eliminating wastage and applying eco-design principles (Mukhtar et al , 2023). Green innovation consists of green product innovation and green process innovation, which positively impact the environmental outcomes (Gangi et al , 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to Chen et al (2006), green innovation refers to designing pro-environmental products and processes that mitigate pollution, recycle waste and preserve energy. It tries to make the product more environmentally friendly through engaging in a gamut of activities such as using greener raw materials, decreasing carbon emissions, reducing the consumption of non-renewable sources of energy, eliminating wastage and applying eco-design principles (Mukhtar et al , 2023). Green innovation consists of green product innovation and green process innovation, which positively impact the environmental outcomes (Gangi et al , 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The scale which will be designed based on previous studies as shown in Table 1. The items will be adapted for proposed questionnaire about ESG practices, innovation orientation and green innovation from Mukhtar, Shad, Woon, et al (2023), Wu (2016) and Chen et al (2006) respectively. The questionnaire items will be validated through pilot test to ensure that the questions are understandable, and respondents can easily complete the survey.…”
Section: Variable Measurement and Data Analysismentioning
confidence: 99%
“…In Addition, Abbasi, et al [16] and Jang and Park [17] reveal that artificial obstacles and gaps created in the games reflect the lower perceived enjoyment of the game and just overcome these issues purchasable in-game content offered to the players. In terms of utilitarian and hedonic perspectives, the usefulness of these in-game content is considered a utilitarian motive whilst enjoyment by the purchase of this content is considered the hedonic motive of in-game content purchase [18][19][20].…”
Section: In-game Virtual Product Purchasementioning
confidence: 99%